Water Condition of Salo River Based on Physical-Chemical Parameters - Rini Sinaga; Clemens Sihotang; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Salo River is one of the Kampar River’s tributaries. Several activities conducted along the river produced pollutant that affects the water quality of the river in general. A research aims to understand the water condition in the Salo River based on physical-chemical parameters was conducted from April to May 2015. There were three stations (St1, St2 and St3) and water samples were taken once/week for a 4 weeks period. Water quality parameters measured were current speed, depths, temperature, transparency, turbidity, pH, DO , CO2, BOD5, nitrate and phosphate content. Results shown that the current speed was 17.5-38 cm/second, depths 29-36.3 cm, temperature 28-28.5 ºC, turbidity 3.34-5.36 FTU, pH 5, DO 6.89- 8.23 mg/L, CO2 7.99-8.99 mg/L, BOD5 2.39-7.29 mg/L, nitrate : 0.0275-0.0555 mg/L, and phosphate 0.0375-0.0525 mg/L. Nitrate and phosphate concentration indicate that the Salo River is in oligotrophic condition.Keywords : Salo River, Water Quality, oligotrophic